2014
DOI: 10.4236/ajps.2014.51021
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Quantitative Trait Loci (QTL) Underlying Protein, Oil, and Five Major Fatty Acids’ Contents in Soybean

Abstract: LG-E (Chr_15), LG-J (Chr_16), and LG-G (Chr_18). The SNP markers closely linked to the QTL reported here will be useful for development of cultivars with altered oil and fatty acid compositions in soybean breeding programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 35 publications
1
39
1
2
Order By: Relevance
“…The protein content in our wild soybean sample averaged about 48%, a higher mean percentage than typically is seen in cultivated soybeans [6, 17]. Consistent with this, Chen and Nelson [33] found that the mean protein level in a wild soybean sample was significantly higher than that in a sample of cultivated soybeans.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The protein content in our wild soybean sample averaged about 48%, a higher mean percentage than typically is seen in cultivated soybeans [6, 17]. Consistent with this, Chen and Nelson [33] found that the mean protein level in a wild soybean sample was significantly higher than that in a sample of cultivated soybeans.…”
Section: Discussionsupporting
confidence: 77%
“…Selection for increased oil content has been practiced for many years, and Zhou et al [19] recently have identified 96 separate selective sweeps located within known oil QTL regions. Oil variability in our wild soybean sample as assessed by the coefficient of variation (10.8) was higher than comparable estimates for cultivated soybeans such as that of 4.74 calculated by Akond et al [6] among recombinant inbred lines.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Therefore, in the current research, several QTLs were found that did not coincide with other researchers groups, but some QTLs were detected previously using the same population MD96-5722 x Spencer [23] [24]. For example, a linoleic acid QTL was detected by others elsewhere [7] on LG N (Chr3) at 4.80 cM position was very close to the QTL for ARG at 4.00 cM; the QTL we identified for SER on LG C2 (Chr6) has been identified for raffinose at the same position (7.20 cM) (unpublished data)and the QTL identified in LG K (Chr 9) for SER and TRP (0.50 cM) were very close to QTL identified in a previous study for the seed content of the isoflavone glycitein (0.60 cM; [20].…”
Section: Amino Acids Qtl Detectionmentioning
confidence: 89%